2015
DOI: 10.1371/journal.pone.0142905
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Multidrug-Resistant Escherichia coli O157 from Goats in the Somali Region of Ethiopia: A Cross-Sectional, Abattoir-Based Study

Abstract: Toxigenic Escherichia coli (E. coli) are an important cause of gastroenteritis in developing countries. In Ethiopia, gastroenteritis due to food-borne disease is a leading cause of death. Yet, there is no surveillance for E. coli O157 and little is known about the carriage of this pathogen in Ethiopia’s livestock. This study aimed to assess the prevalence and levels of antimicrobial resistance of E. coli O157 in goat meat, feces, and environmental samples collected at a large abattoir in the Somali region of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
46
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 13 publications
10
46
2
Order By: Relevance
“…Further, cefotaxime and ciprofloxacin only elicited a significant effect on some of the E.coli O157 strains and only intermediate effects on others. This is in agreement with previous reports on antimicrobial resistance patterns of E. coli O157:H7 isolates from animal and human sources [74][75][76]. Further, previous studies on antibiotic resistance of bacteria in the feces of slaughtered ruminants have reported that isolates showed higher resistance or multiple resistance [42,72,73].…”
Section: Discussionsupporting
confidence: 92%
“…Further, cefotaxime and ciprofloxacin only elicited a significant effect on some of the E.coli O157 strains and only intermediate effects on others. This is in agreement with previous reports on antimicrobial resistance patterns of E. coli O157:H7 isolates from animal and human sources [74][75][76]. Further, previous studies on antibiotic resistance of bacteria in the feces of slaughtered ruminants have reported that isolates showed higher resistance or multiple resistance [42,72,73].…”
Section: Discussionsupporting
confidence: 92%
“…However, effectively treating E. coli O157:H7/H-infections is challenging, due to differing opinions presented by various investigators [55]. Many studies have reported an increasing incidence of multi-drug resistant E. coli O157:H7/H-strains isolated from the feces of slaughtered ruminants [56][57][58]. Our results show that all isolated strains were susceptible to antibiotics; cefotaxime, chloramphenicol, cipro oxacin, nor oxacin, and polymyxin B.…”
Section: Discussionmentioning
confidence: 78%
“…In developing countries, including Ethiopia, animals are commonly slaughtered and dressed under unhygienic conditions and this further compromises the microbiological quality and safety of the meat obtained from the animals [29, 30]. This can consequently risk the health of consumers.…”
Section: Introductionmentioning
confidence: 99%
“…This can consequently risk the health of consumers. In the presence of all the above situations, so far there are only few studies which addressed to assess the prevalence and distribution of E. coli O157:H7 in humans, animals or in foods of animal origin in Ethiopia [5–8, 30]. Therefore, the objectives of the present study were: (i) to isolate and identify E. coli O157:H7 from cattle feces, carcasses and contact surfaces at abattoir and butcher shops, (ii) to determine to what extent the abattoirs and butcher house environments serve as sources of E. coli O175:H7 and (iii) to determine the antimicrobial susceptibility pattern of the isolates.…”
Section: Introductionmentioning
confidence: 99%